Keberkesanan kaunseling kelompok strategi adaptasi Motivational Interviewing (AMI) ke atas kesediaan untuk berubah dan penghargaan kendiri dalam kalangan penghuni di Pusat Koreksional Labuan - Puteri Hayati Megat Ahmad; Nurul Hudani Md Nawi; Suardi Sudi (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study aims to determine the effectiveness of the group counselling strategy Adaptation Motivational Interviewing, (AMI) on Readiness to Change and Self-Esteem among drug users in Labuan Correctional Centre. The treatment module of group counselling AMI was used as a treatment guideline in a group counselling session. The research tools used were The Stage of Change Readiness and Treatment Eagerness Scale, SOCRATES and Rosenberg Self-Esteem Scale, RSES to assess Readiness to Change (Identification, Uncertainty and Planning, Recognition, Ambivalence and Taking Steps) and Self-Esteem. A total of 50 inmates were involved as a treatment group using one group's quasi-experimental pre-test and post-test design. The findings of the study showed that there were significant differences in the readiness to change (Identification, Uncertainty and Planning, Recognition, Ambivalence and Taking Steps) and self-esteem of the treatment group. From the aspect of correlation, there is a positive and significant relationship between identification and planning with self -esteem while Uncertainty shows a negative and significant relationship with the subject's self-esteem. This study provides new input to the Malaysian Prison Department, especially in providing the best treatment and rehabilitation services for drug addicts. The implication is that group counselling induces the success in the treatment and rehabilitation process of drug addicts and offenders in the long run as has been implemented and proven by many foreign countries that recognize the effectiveness of AMI and MI.